Training and simulation of the German A2-Level writing exam for SMA/SMK students - Novia Anjani Dewi; Ending Khoerudin; Lucky Herliawan Y. A.; Tri Indri Hardini (Universitas Pendidikan Indonesia, 2025)
This research is part of the Community Service Program (PkM) designed to help high school students in the Bogor area improve their skills in taking the A2 level German writing exam (Goethe-Zertifikat A2). This activity is also part of the preparation for the National German Language Olympics. The problem arises due to students' lack of understanding of the question and digital exam formats. Therefore, providing tools and training that can help overcome technical challenges and improve German writing skills is essential. This research aims to develop a training program and exam simulation based on the Moodle LMS (simujerman.com) specifically for writing skills. The method applied in this training program is a blended learning approach. The materials covered include an introduction, exam format, targeted practice questions, and simulations to improve students' readiness for the actual exam at the Olympiad. The evaluation results showed a significant improvement in students' writing skills. Thus, using the Moodle LMS has proven to facilitate self-directed learning while enhancing the effectiveness of preparation for the German language writing skills exam at the A2 level. The findings of this paper are expected to serve as a model for the development of technology-based learning, particularly in foreign language instruction. Abstrak Penelitian ini merupakan bagian dari Program Pengabdian kepada Masyarakat (PkM) yang dirancang untuk membantu siswa SMA/SMK di wilayah Bogor meningkatkan kemampuan mereka dalam menghadapi ujian menulis bahasa Jerman tingkat A2 (Goethe-Zertifikat A2). Kegiatan ini juga menjadi bagian dari persiapan untuk Olimpiade Bahasa Jerman tingkat Nasional. Permasalahan muncul karena kurangnya pemahaman siswa terhadap bentuk soal dan format ujian digital. Oleh karena itu, pentingnya untuk menyediakan alat dan pelatihan yang dapat membantu mengatasi kendala teknis serta meningkatkan kemampuan menulis bahasa Jerman. Tujuan penelitian ini berfokus dalam mengembangkan program pelatihan dan simulasi ujian berbasis LMS Moodle (simujerman.com) khusus untuk keterampilan menulis. Metode yang diterapkan dalam program pelatihan ini adalah dengan pendekatan blended learning. Materi yang disampaikan mencakup pengenalan, format ujian, latihan soal terarah, serta simulasi yang bertujuan untuk meningkatkan kesiapan siswa dalam menghadapi ujian sesungguhnya di olimpiade. Hasil evaluasi kegiatan menunjukkan adanya peningkatan kemampuan menulis siswa secara signifikan. Dengan demikian, pemanfaatan LMS Moodle ini terbukti memberikan kemudahan dalam pembelajaran mandiri sekaligus meningkatkan efektivitas dalam persiapan ujian keterampilan menulis bahasa jerman tingkat A2. Hasil dari penulisan karya ilmiah ini diharapkan dapat menjadi model untuk pengembangan pembelajaran berbasis teknologi, terutama dalam pengajaran bahasa asing. Kata Kunci: blended learning; LMS moodle; olimpiade bahasa Jerman; ujian menulis bahasa Jerman